Impact of Particle Size Distribution on Performance of Lithium‐Ion Batteries - Bläubaum, Lars; Röder, Fridolin; Nowak, Christine; Chan, Hoon Seng; Kwade, Arno; Krewer, Ulrike (ChemElectroChem, 2020)
This work reveals the impact of particle size distribution of spherical graphite active material on negative electrodes in lithium‐ion batteries. Basically all important performance parameters, i. e. charge/discharge characteristics, capacity, coulombic and energy efficiencies, cycling stability and C‐rate capability are shown to be affected by distribution shapes. A narrow distribution with smaller particles results in better cell performance than broader and coarser distributions. However, particle size reduction has a limitation as extremely small particles show negative effect in performance. More critically, independent of the particle size distribution, the existence of coarse particles are found to promote lithium plating, which lowers cell performance and threatens the safety of battery operation. Furthermore, impedance analysis and cycling stability show huge differences for different electrodes. Our study shows that a better understanding of the influence of particle size distribution is an important base to engineer electrodes with higher C‐rate capability, higher performance, and lower safety risk due to lithium plating. Distribution matters: The particle size and their distributions of graphite negative electrodes in lithium‐ion batteries where investigated. Significant differences in performance and aging between the material fractions were found. The trend goes to medium sized particles and narrow distributions.